Long‐term deepened snow promotes tundra evergreen shrub growth and summertime ecosystem net CO2 gain but reduces soil carbon and nutrient pools. (2nd March 2018) - Christiansen, Casper T.; Lafreniére, Melissa J.; Henry, Gregory H. R.; Grogan, Paul
Abstract: Arctic climate warming will be primarily during winter, resulting in increased snowfall in many regions. Previous tundra research on the impacts of deepened snow has generally been of short duration. Here, we report relatively long‐term (7–9 years) effects of experimentally deepened snow on plant community structure, net ecosystem CO2 exchange (NEE), and soil biogeochemistry in Canadian Low Arctic mesic shrub tundra. The snowfence treatment enhanced snow depth from 0.3 to 1 m, increasing winter soil temperatures by 3°C, but with no effect on summer soil temperature, moisture, or thaw depth. Nevertheless, shoot biomass of the evergreen shrub Rhododendron subarcticum was near‐doubled by the snowfences, leading to a 52% increase in aboveground vascular plant biomass. Additionally, summertime NEE rates, measured in collars containing similar plant biomass across treatments, were consistently reduced 30% in the snowfenced plots due to decreased ecosystem respiration rather than increased gross photosynthesis. Phosphate in the organic soil layer (0–10 cm depth) and nitrate in the mineral soil layer (15–25 cm depth) were substantially reduced within the snowfences (47–70 and 43%–73% reductions, respectively, across sampling times). Finally, the snowfences tended ( p = .08) to reduce mineral soil layer C% by 40%, but with considerable within‐ and among plot variation due to cryoturbation across the landscape. These results indicate that enhanced snow accumulation is likely to further increase dominance of R. subarcticum in its favored locations, and reduce summertime respiration and soil biogeochemical pools. Since evergreens are relatively slow growing and of low stature, their increased dominance may constrain vegetation‐related feedbacks to climate change. We found no evidence that deepened snow promoted deciduous shrub growth in mesic tundra, and conclude that the relatively strong R. subarcticum response to snow accumulation may explain the extensive spatial variability in observed circumpolar patterns of evergreen and deciduous shrub growth over the past 30 years. Abstract : Climate warming in the Arctic will be primarily during the winter season, resulting in increased snowfall in many regions. Here, we report that long‐term (7–9 years) experimentally deepened snow increased evergreen Rhododendron subarcticum shoot biomass and overall summertime ecosystem CO2 gain, while having no effect on deciduous shrub growth, in mesic birch hummock tundra. Surprisingly, soil biogeochemistry was generally reduced or unchanged in the snowfence treatment. These observations may help explain the extensive spatial variability in observed patterns of evergreen and deciduous shrub growth across the Arctic over the past 30 years.